2019
DOI: 10.1080/16078454.2019.1662200
|View full text |Cite
|
Sign up to set email alerts
|

A systematic literature review on the use of platelet transfusions in patients with thrombocytopenia

Abstract: Objective: Investigate globally, current treatment patterns, benefit-risk assessments, humanistic, societal and economic burden of platelet transfusion (PT). Methods: Publications from 1998 to June 27, 2018 were identified, based on databases searches including MEDLINE®; Embase and Cochrane Database of Systematic Reviews. Data from studies meeting pre-specified criteria were extracted and validated by independent reviewers. Data were obtained for efficacy and safety from randomized controlled trials (RCTs); da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 185 publications
0
13
0
1
Order By: Relevance
“…However, platelet transfusion is not recommended for patients receiving antiplatelet therapy who have cerebral hemorrhage that does not require surgical treatment [167,168]. The use of platelet count as an indication for platelet transfusions has not been shown to improve the outcomes of critical care patients [169,170]. The use of platelet function parameters to guide platelet transfusion in critical care patients with thrombocytopenia may be beneficial for improving the outcomes of these patients [171][172][173].…”
Section: Alternative Treatment Recommendation 22: Platelet Transfusiomentioning
confidence: 99%
“…However, platelet transfusion is not recommended for patients receiving antiplatelet therapy who have cerebral hemorrhage that does not require surgical treatment [167,168]. The use of platelet count as an indication for platelet transfusions has not been shown to improve the outcomes of critical care patients [169,170]. The use of platelet function parameters to guide platelet transfusion in critical care patients with thrombocytopenia may be beneficial for improving the outcomes of these patients [171][172][173].…”
Section: Alternative Treatment Recommendation 22: Platelet Transfusiomentioning
confidence: 99%
“…Patients with primary immune thrombocytopenia (ITP) who exhibit severe thrombocytopenia and/or significant bleeding require treatment with corticosteroids and/or intravenous immunoglobulin (IVIG) as first-line therapy [1, 2]. Predicting the response to corticosteroids may help to avoid unnecessary therapy, and side effects, and facilitate the use of optional therapeutic agents.…”
Section: Introductionmentioning
confidence: 99%
“…For severe COVID-19 patients who are not bleeding, platelet transfusion is recommended if the platelet count is < 20 × 10 9 /L; for severe COVID-19 patients who intend to undergo a lumbar puncture or present with active bleeding, platelet transfusion is recommended if the platelet count is < 50 × 10 9 /L; for severe COVID-19 patients undergoing ECMO, platelet transfusion is recommended if the platelet count is < 80 × 10 9 /L [30,37]. Previous studies have shown that the use of platelet count as an indication for platelet transfusions has not been shown to improve the outcomes of critically ill patients [38]. However, the use of platelet function indicators to guide platelet transfusions in critically ill patients with thrombocytopenia may be beneficial for improving the outcome of these patients [39].…”
Section: Replacement Treatmentmentioning
confidence: 99%